2006
DOI: 10.1101/gr.5012006
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Yellow/Major Royal Jelly Protein family and the emergence of social behavior in honey bees

Abstract: The genomic architecture underlying the evolution of insect social behavior is largely a mystery. Eusociality, defined by overlapping generations, parental brood care, and reproductive division of labor, has most commonly evolved in the Hymenopteran insects, including the honey bee Apis mellifera. In this species, the Major Royal Jelly Protein (MRJP) family is required for all major aspects of eusocial behavior. Here, using data obtained from the A. mellifera genome sequencing project, we demonstrate that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
258
0
38

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 269 publications
(322 citation statements)
references
References 68 publications
14
258
0
38
Order By: Relevance
“…We further expanded our analyses to genes implicated in A. mellifera caste differentiation identified by previous studies of gene expression (33)(34)(35)(36)(37)(38). Again we found that caste-specific genes overwhelmingly belong to the high-CpG class ( Table 3).…”
Section: Genes Whose Expression Is Strongly Biased Toward Specific Camentioning
confidence: 89%
“…We further expanded our analyses to genes implicated in A. mellifera caste differentiation identified by previous studies of gene expression (33)(34)(35)(36)(37)(38). Again we found that caste-specific genes overwhelmingly belong to the high-CpG class ( Table 3).…”
Section: Genes Whose Expression Is Strongly Biased Toward Specific Camentioning
confidence: 89%
“…The most dominant protein found in honey produced by two honeybees within the genus Apis is rayalactin or Major Royal Jelly Protein 1 (MRJP1) (Won et al, 2008). One of the many functions of this protein involves the stimulation of reproductive maturation in honeybees (Drapeau et al, 2006). However, the sole action of MRJP1 in honeybees was found to be responsible for queen differentiation in which juvenile hormone titers increased and vitellogenin genes (precursors of yolk protein) were expressed at a higher rate.…”
Section: Discussionmentioning
confidence: 99%
“…Apalbumin 1 was reported to constitute 48% of the RJ proteins and also to be present in honey (Scarselli et al, 2005). The genes of those proteins were recently identified (Schmitzova et al, 1998;Drapeau et al, 2006) with the unveiling of the honeybee complete genome, and they are suggested to be multifunctional, performing diverse nutritional, physiological and developmental roles and affecting various tissues, including the brain (Drapeau et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For up to 3 days, the larvae are supplied with royal jelly (RJ) that is secreted by young worker bees (nurse bees) in the hive. Thereafter, only larvae designated to become queens receive RJ, while a mixture of honey, pollen and water is fed to larvae selected to become workers (Drapeau et al, 2006).…”
Section: Introductionmentioning
confidence: 99%